Minimally invasive combined approach robotic thymectomy and transcervical total thyroidectomy. Issue 4 (22nd April 2022) - Crudeli, Connor; Reid, Lisa; Burg, Jennifer; Shersher, David
Abstract : Myasthenia gravis (MG) is the most common autoimmune disorder affecting the neuromuscular junction in the USA. It is not uncommon for these patients to have concomitant autoimmune diseases including autoimmune thyroid disease. We describe here our method of performing a reproducible robotically assisted one-stage thymectomy and thyroidectomy. An African-American woman presented to our institution with a medical history of hypertension, morbid obesity, type 2 diabetes mellitus, symptomatic MG and symptomatic non-toxic substernal multinodular goitre. A one-stage minimally invasive right-sided robotic radical thymectomy and a transcervical total thyroidectomy with excision of the substernal goitre was successfully performed. The treatment of thyroid and thymus pathologies varies drastically from medical observation to surgery. This combined approach surgery clearly benefits the patient by offering similar operative time, fewer operative and postoperative recovery experiences, decreased anaesthesia risks associated with MG patients through fewer intubations, and a faster return to baseline function.